PENGARUH METODE KERJA KELOMPOK TERHADAP HASIL BELAJAR SISWA PELAJARAN IPAS DI KELAS IV SD NEGERI 8 PAJAR BULAN - Imam Subhi; Delvi Bella Reza; Esah (LPPM Universitas Cipta Mandiri, 2024)
The aim of this research is to find out whether the group work method can improve student learning outcomes in natural and social science subjects and to find out how big a factor the group work method is in student learning outcomes in natural and social science subjects at the 8 Pajar Bulan State Elementary School. This research methodology uses quantitative research methods. In sampling, researchers used a purposive sampling method. Data collection techniques use observation, questionnaires and documentation. The results of this research are to see how much influence the group work method has on student learning outcomes in natural and social science lessons in class IV of the 8 Pajar Bulan State Elementary School, it can be seen from the coefficient of determination test which has an r square result of 0.359 which shows that the group work method has an influence of 35.9% on student learning outcomes. And based on testing from the results of data analysis carried out regarding the influence of group work methods on student learning outcomes in natural and social science lessons, it can be concluded that group work methods have a positive and significant effect on student learning outcomes in natural and social science lessons and can also be concluded. it is said that ha is accepted, which can be seen from the hypothesis test which has a significant value of 0.002, where the result is <0.05.